(Still) Up to No Good: Reconfiguring Worker Resistance and Misbehaviour in an Increasingly Unorganized World - van den Broek, Diane; Dundon, Tony (Relations industrielles / Industrial Relations, 2012)
SummaryThe way worker resistance and misbehaviour have been analyzed has undergone significant transformation over the past few decades. While researchers have observed the quantitative decline of formal or organized forms of industrial relations conflict, others have highlighted the emergence of informal and individualized (mis)behaviours. There have been a range of reasons advanced to explain both the decline in industrial disputes and in the lineal approaches to analyze workplace conflict. This article cautions the increasing tendency to analyze resistance and misbehaviour in an institutional vacuum. Drawing on longitudinal research across multiple organizational settings in Australia and Britain, the article identifies the longevity of institutional and structural factors to explain workplace behaviours, particularly among weakly organized workers. The evidence presented in this paper emphasizes the need to analyze employee resistance within its institutional context. The range of behaviours identified here in many non- or anti-union settings were shaped by the changing structural and institutional workplace regime: by sector, size, structure or managerial strategy (among others). By recognizing the importance of context and place, we argue that what is often portrayed as types of misbehaviour substitute for more assertive forms of resistance by workers who are vulnerable in the labour market or denied access to traditional collective structures of representation.